The Relationship Between Learning Interest Of Students Toward Learning Achievement At Mts Al Mafas - Jaya; Yunus H, Ismail (Universitas Madako Tolitoli, 2023)
This research aimed to determine the significant correlation between learning interests and students' learning achievement at MTs Al Mafaz. The research design is a quantitative analysis. The researchers used purposive sampling. The samples comprised 15 students in grade seven, and the data were obtained from the questionnaire and documentation. The technique used to analyze the data is simple correlation with SPSS 21 v.21 Program. The result of the research showed that the value of the Coefficient Correlation 0,01 means that there is no correlation between parents' attention and learning achievement, it was a very weak correlation based on the table interpretation of correlation, and it is based on the value significance Sig. (2-tailed) The correlation between learning interest and students' learning achievement is 0,957 > 0,05. There is no significant correlation between learning interest and students' learning achievement. The hypothesis is Null Hypothesis (Ho) is accepted, and Hypothesis Alternative (Ha) is rejected.